2022
DOI: 10.3390/biology11060880
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Proliferation from Fetal- to Adult- and from Normal- to Hypertrophy and Failing Hearts

Abstract: The cardiomyocyte undergoes dramatic changes in structure, metabolism, and function from the early fetal stage of hyperplastic cell growth, through birth and the conversion to hypertrophic cell growth, continuing to the adult stage and responding to various forms of stress on the myocardium, often leading to myocardial failure. The fetal cell with incompletely formed sarcomeres and other cellular and extracellular components is actively undergoing mitosis, organelle dispersion, and formation of daughter cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 326 publications
0
9
0
Order By: Relevance
“…Consistent with the animal studies, human in vitro models of high glucose injury showed that both podocytes and cardiomyocytes exhibited a significant increase in average surface area after high glucose injury, whereas T3 reversed this response ( Figures 3 G and 3H). Cultured cardiomyocytes stressed with high glucose concentration not only had a larger cell area but also adopted a “fetal-like” round shape 28 , 29 which was normalized by T3 treatment ( Figure 3 I).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the animal studies, human in vitro models of high glucose injury showed that both podocytes and cardiomyocytes exhibited a significant increase in average surface area after high glucose injury, whereas T3 reversed this response ( Figures 3 G and 3H). Cultured cardiomyocytes stressed with high glucose concentration not only had a larger cell area but also adopted a “fetal-like” round shape 28 , 29 which was normalized by T3 treatment ( Figure 3 I).…”
Section: Resultsmentioning
confidence: 99%
“…Troponin I regulates the state of thin and thick filaments in the sarcomere [63], inhibiting muscle contraction in the absence of calcium. The slow skeletal muscle cardiac troponin I isoform is predominant in the developing fetal heart, replaced by the mature sarcomere cardiac isoform at around birth [64]. In congenital heart defects, there is a delay in the expression of the latter isoform [65].…”
Section: Discussionmentioning
confidence: 99%
“…At early developmental stages, when cardiomyocytes are proliferative, cardiomyocytes contain fewer and less-organized sarcomeres. 4,13,14 During cardiomyocyte maturation, new sarcomeres are added to the preexisting myofibrillar network, and collectively, sarcomeres undergo structural changes as adult isoforms of sarcomeric proteins replace the fetal isoforms. For example, mammalian cardiac MHC (myosin heavy chain) proteins have 2 isoforms, α-isoform ( MYH6 ) and β-isoform ( MYH7 ), encoded by 2 distinct genes.…”
Section: Key Cellular Characteristics In Pmdmentioning
confidence: 99%